2022
DOI: 10.1016/j.ejon.2021.102079
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and related factors in colorectal cancer patients: A systematic review

Abstract: To explore resilience and its related factors in adult colorectal cancer patients. Methods: Three databases (CINAHL, Scopus and PubMed) were searched for literature published from January 2009 to February 2021 using the terms colorectal and resilience or resilient or resiliency. The review was registered with PROSPERO and followed the PRISMA statement guidelines. Results: The studies (n = 11) showed that most colorectal cancer patients exhibit moderate levels of resilience. Resilience was identified as a media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 61 publications
0
18
0
1
Order By: Relevance
“…Resilience, or the ability to recover when faced with stressful situations (Sihvola et al, 2022), is also linked to the caregiver's role. In fact, resilience increases care readiness (Lester et al, 2020; Zale et al, 2018), and having the ability to adequately cope with issues decreases a caregiver's burden and anxiety (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Resilience, or the ability to recover when faced with stressful situations (Sihvola et al, 2022), is also linked to the caregiver's role. In fact, resilience increases care readiness (Lester et al, 2020; Zale et al, 2018), and having the ability to adequately cope with issues decreases a caregiver's burden and anxiety (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…52 In a recent systematic review and inductive content analysis of literature pertaining to resilience in colorectal cancer patients, resilience was associated with a variety of factors, including social support, hope, mental and physical burden, quality of life, and post-traumatic growth. 53 Other research has shown that cancer patients with higher resiliency report lower levels of emotional distress 54 and better quality of life. 55 Recently, Dionne-Odom et al found higher caregiver-reported resilience was associated with higher caregiver preparedness.…”
Section: Influential Othersmentioning
confidence: 99%
“…Colorectal cancer is a type of malignancy that affects the large intestine and rectum regions. 4 In 2020, the number of death caused by colorectal was 506,449 in Asia, 244,824 in Europe, 63,987 in North America and 69,435 in Latin America and the Caribbean. 1 Colorectal cancer statistics are expected to grow with a morbidity estimation of 1.1 million worldwide by 2030.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…3 CRC is a type of malignancy that affects the large intestine and rectum regions. 4 It is caused by the deactivation of the p53 pathway or adenomatous polyposis coli gene, the accumulation of mutations such as in K-ras, the transforming growth factor-beta pathway and the genesis of small polyps. The American Joint Committee on Cancer divided CRC into five phases with different treatment strategies for each stage.…”
Section: Introductionmentioning
confidence: 99%